SIMULATION MODELING OF TELECOMMUNICATION SYSTEMS ACCESSABILITY - Терентьєва, Ірина Євгенівна (Science-based technologies, 2019)
The article considered the telecommunication systems with permanent and intermittent failures and the main parameters for determining their accessibility. The generalized algorithm of simulation modeling of the random process of the telecommunication system equipment operation and maintenance was proposed using the Monte Carlo method. The simulation modeling of the operation and maintenance of the equipment of the telecommunication system was carried out. Duration and number of iterations were selected taking into account the infinite interval of observation of the random process. It was shown that the results of simulation modeling have high convergence of statistical and analytical results obtained during mathematical modeling of the process of operation and maintenance of equipment of the telecommunication system at the exponential distribution of the time to failure, the relative deviation did not exceed 3%. It was illustrated that the results of simulation modeling demonstrate the approximation of the readiness coefficient to its value, calculated on the analytical expression, with the increase in the number of implementations of the random operation of the maintenance and maintenance of the equipment of the telecommunications system. The proposed simulation modeling algorithm can be used both when there is the problem of establishing an analytical relationship between the parameters of the telecommunication system equipment for its accessibility determination, and for checking the adequacy of the developed mathematical models of the process of operation and maintenance of modern telecommunication systems and networks.